Audit quality and decision-making in small companies. Issue 9 (28th August 2014) - Ojala, Hannu; Niskanen, Mervi; Collis, Jill; Pajunen, Kati
Abstract : Purpose: This paper focuses on economic consequences of audit outcomes by investigating the concept of audit quality operationalized as seven components of audit benefits to owner-managers of small companies. Design/methodology/approach: We analyse survey data collected in 2013 from 642 small private companies above the audit exemption threshold in Finland. Findings: We find no significant association between engagement of a Big 4 auditor (proxy for audit quality) and any of the audit benefits tested. However, our results provide consistent evidence of a positive relationship between the owner-manager's perception of the competence and reliability of the external accountant and the perceived benefits of audit. We also find that companies which do not incorporate e-processes in the accounting system are more likely to value the internal control benefits provided by audit. Research limitations/implications: Small business surveys suffer from poor response rates. To some extent we overcame this problem by using two focused sampling frames and reminders. Care must be taken when generalizing our results, as the definition of 'small' varies across jurisdictions. Originality/value: By focusing on small private companies, the research contributes to the audit quality literature. Contrary to studies of listed companies, we conclude that use of a Big 4 auditor is not a sufficient surrogate for audit quality in small companies. We go beyond aggregate measures of audit quality used in previous studies and identify specific audit benefits.